The Role of Dual Energy CT in Evaluating Hemorrhagic Complications at Different Stages After Thrombectomy - Liu, Keqin; Jiang, Lin; Ruan, Jie; Xia, Wenqing; Huang, Huan; Niu, Guozhong; Yan, Shenqiang; Yin, Congguo (Frontiers in Neurology, 2020)
Background: Contrast medium extravasation can mimic hemorrhage after endovascular thrombectomy (EVT). Dual energy CT (DECT) has potential to distinguish hemorrhage from iodine contrast. Methods: We retrospectively examined clinical and radiological data from 106 consecutive acute ischemic stroke patients who received EVT and underwent DECT immediately and 24 hours after EVT. Iodine overlay map, virtual non-contrast and mixed images are reconstructed. Results: With the use of DECT, the proportion of all patients diagnosed with hemorrhagic transformation on mixed images immediately after EVT was reduced from 74.5% (79 of 106) to 10.4% (11 of 106), with a very poor consistency (κ = 0.076, p = 0.041). Correspondingly, hemorrhagic transformation on mixed images 24 hours after EVT was reduced from 41.5% (44 of 106) to 30.2% (32 of 106), with a moderate consistency (κ = 0.757, p < 0.001). Conclusions: Both DECT immediately and 24 hours after EVT changes the diagnosis of hemorrhagic transformation in a considerable proportion of acute ischemic stroke patients with EVT. This could affect decision-making of antithrombotic strategy.